Reliance of Kurdish Satellite channels on Television Programs to Spread Social Awareness: (An Analytical Study) - Bashdar Husen Muhammed; Nazakat Hussein HamaSaeed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Kurdish television channels are one of the most influential media tools, broadcasting programs that have a social dimension to present issues and problems. This study aims to determine the extent to which Kurdish television channels rely on television programs related to spreading social awareness. This research is descriptive, the researcher used the method (of content analysis). The subject of this research is Kurdish television channels. The sample of the research is the programs (Psychology and Phenomena) on Kurdistan 24 and (File and Phenomenon) on Kurdsat News. The findings showed that Kurdish television channels rely heavily on television programs to comment on issues such as "Social phenomena" and "the existence of problems" were the most important topics of the programs. The social issues presented in the programs were "social awareness" and "the impact of media and social media." Regarding the way social issues are discussed, the programs primarily emphasize the idea of identifying the causes of problems and presenting solutions.